Analysis of the impact of the Covid-19 pandemic on people's mental health - Nurlaili Ramli; Anita Anita (Institute of Computer Science (IOCS), 2022)
The COVID-19 pandemic has had a major impact on physical health and psychological or mental health. The number of deaths that are increasing day by day due to the corona virus not only causes physical symptoms and illnesses, but also has a major impact on mental health. This study aims to determine what factors affect people's mental health and determine the effect of COVID-19 on people's mental health. This study is a systematic review using online databases namely Scholar, ScienceDirect, and ProQuest. The keywords used were Impact of the Covid-19, people's mental health. The selection process used the PRISMA protocol, resulting in 15 articles that met the inclusion criteria. The results of the review analysis revealed the impact of the pandemic on mental health, causing several disorders such as excessive fear and anxiety about anxiety for themselves and those closest to them; changes in sleeping and eating patterns, feeling depressed and having trouble concentrating; bored and stressed from being constantly at home, especially children; drug and alcohol abuse; and the emergence of psychotic disorders. COVID-19 has had a major impact on people's physical and mental health and alcohol abuse; and the emergence of psychotic disorders. COVID-19 has had a major impact on people's physical and mental health.